AB0091 Decreased expression of bcl6 in peripheral blood monocytes from rheumatoid arthritis patients. (23rd January 2014) - Zou, C.-J.; Mo, Y.-Q.; Zhu, L.-J.; Wei, X.-N.; Zheng, D.-H.; Ma, J.-D.; Li, Y.-H.; Chen, L.-F.; Dai, L.
Abstract : Background: Rheumatoid arthritis (RA) is a common chronic inflammatory disease which could lead to joint destruction and disability. Osteoclasts are essential for bone resorption and play key roles in joint destruction in RA. A recent research on mice suggested that B cell lymphoma 6 (Bcl6) is a negative regulator of osteoclastogenesis, and Bcl6 deficiency facilitates osteoclast formation. B lymphocyte–induced maturation protein-1 (Blimp1) regulates Bcl6 expression and osteoclastogenesis. However, the effect of Bcl6 and Blimp1 on osteoclastogenesis in RA patients is unknown. Objectives: To investigate the expression of Bcl6 in peripheral blood monocytes (PBMs, osteoclast precursors) and its correlation with disease activity and radiographic joint destruction in RA. Methods: PBMs were isolated from 24 RA patients and 16 healthy controls matched with age and gender, and identified by flow cytometry with CD14 and CD3 markers. The expression of Bcl6 protein was detected by immunofluorescence. Bcl6 and Blimp1 mRNA expression in PBMs was determined by real-time PCR and correlated with clinical parameters which reflect disease activity and radiographic joint destruction (Sharp score). Results: (1) Immunofluorescence staining showed significantly decreased expression of Bcl6 in PBMs from RA patients than healthy controls (1.76±0.08 vs 1.88±0.03 AU/mm 2, p =0.009). (2) Bcl6 and Blimp1 mRNA expression in PBMs was decreased significantly in RA patients than in healthy controls (χ 2 =9.733, p =0.002; χ 2 =9.334, p =0.001, respectively). (3) To exclude the influence of medication, 12 treatment-naïve RA patients who had never been treated with disease-modifying antirheumatic drugs or glucocorticoids were analyzed. Bcl6 and Blimp1 mRNA expression in PBMs was decreased significantly in treatment-naïve RA patients, compared with that in healthy controls (χ 2 =12.452, p <0.001; χ 2 =8.077, p =0.003, respectively). (4) Spearman's rank order correlation showed that Bcl6 mRNA expression in PBMs from RA patients was positively correlated with joint space narrowing subscore and Blimp1 mRNA expression (r=0.488, p =0.021; r=0.639, p =0.001, respectively), but not significantly correlated with clinical parameters including rheumatoid factor, C-reactive protein, anti-cyclic citrullinated peptide antibody, erythrocyte sedimentation rate, the 28-joint tender and swollen joint count and the disease activity score in 28 joints (DAS28) with three variables including CRP (DAS28(3)-CRP) (all p >0.05). Conclusions: Our results showed that Bcl6 expression was decreased in PBMs in RA patients, which implied that Bcl6 may be involved in osteoclastogenesis in RA. Further studies are needed to establish the mechanisms of Bcl6 in osteoclatogenesis and joint destruction in RA. Acknowledgements: This work was supported by the Chinese National Natural Science Research Grant (grant no.30972742 and 81001334) and the Natural Science Research Grant of Guangdong Province, China (grant no. 9151008901000130 and 10451008901004542). Disclosure of Interest: None Declared